(untitled) (Journal of Tikapur Multiple Campus, 2024)
Participatory Action Research (PAR) is widely acknowledged for its substantial role in the field of English Language Teaching and Learning (ELT), fostering collaborative and active engagement, and a culture of reflective practice. This study explores the perceptions held by English teachers regarding the contribution of PAR to the efficacy of English language teaching and learning. Additionally, the study seeks to scrutinize the strategies employed by teachers in implementing PAR to augment the teaching and learning of English within the classrooms. Through the discussion of data obtained from in-depth interviews conducted with three English language teachers form three secondary level school of Kailali district and a comprehensive review of theoretical and empirical literature, this paper reveals the intricate challenges associated with the implementation of PAR, despite the positive disposition of teachers towards this approach. The findings highlight the belief held by English language teachers that PAR not only facilitates proficient teaching and learning of English as a foreign or second language but also assumes a pivotal role in the ongoing professional development of educators. Moreover, this paper accentuates the significance of PAR in ELT, emphasizing its capacity to empower both teachers and learners, instill contextual relevance, promote a sense of community, address equity concerns, and contribute substantively to the perpetual enhancement of language teaching and learning practices.